High energy trauma with complex fracture of the right tibial plateau, compartment syndrome and infection in a professional freestyler motorcyclist - Pedrazzini, Alessio; Garzia, Alice; Bertoni, Nicola; Yewo Simo, Henry; Bisaschi, Roberto; Medina, Vanni; Pogliacomi, Francesco (Acta Biomedica Atenei Parmensis, 2020)
Background and aim of the work: High-energy tibial plateau fractures are complex lesions that may be associated with extensive soft tissue damages and severe complications, such as compartment syndrome and neurological injuries. This case report interests a professional motocross freestyler with complex tibial plateau fracture associated to compartment syndrome and partial common peroneal nerve impairment which complicated with a dehiscence of the surgical wound and infection after plate and screws fixation. One year later, despite the complexity of the fracture, the gravity of the soft tissue lesions and subsequent complications, the patient healed. This satisfactory result depended on the correct management in terms of type of treatment and timing.